Morphology of pterygium (Texas Journal of Medical Science, 2023)
This article details the morphology of pterygium, eastern regional eye care program in eastern Nepal, surgical steps for pterygium removal, amniotic membrane transplantation, procedure pterygium excision with conjunctival autograft.